2022
DOI: 10.1029/2022gl099101
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Dropsondes to Assess Moist Static Energy Variability in Tropical Cyclones

Abstract: Organized convective systems like tropical cyclones (TCs) (Emanuel, 2003) produce much of the extreme weather in the tropics, and influence large-scale patterns of circulation, moisture, and radiation (Khairoutdinov & Emanuel, 2010;Silvers & Robinson, 2021;Wing et al., 2020). Idealized modeling studies have improved our understanding of convective organization, including the spontaneous self-aggregation that arises due to interactions between clouds, water vapor, radiation, and circulations (e.g., Held et al. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
0
0
0
Order By: Relevance
“…These variables are indicative of convective processes and enhanced moisture in the atmospheric column. The average moist static energy (MSE) over the entire column in TC's core region is an important feature reflecting the oscillation of moisture related to organized convective activities [57], and enhanced MSE signifies intensified TC intensity [58]. Thus, it can be observed that enhanced convective processes during 3 days before TC formation can play a crucial role in determining the TC genesis, as forecasted by the WRF-LETKF ensemble assimilation system.…”
Section: Composite Analyses Of Environment Conditions Favoring Tropic...mentioning
confidence: 99%
“…These variables are indicative of convective processes and enhanced moisture in the atmospheric column. The average moist static energy (MSE) over the entire column in TC's core region is an important feature reflecting the oscillation of moisture related to organized convective activities [57], and enhanced MSE signifies intensified TC intensity [58]. Thus, it can be observed that enhanced convective processes during 3 days before TC formation can play a crucial role in determining the TC genesis, as forecasted by the WRF-LETKF ensemble assimilation system.…”
Section: Composite Analyses Of Environment Conditions Favoring Tropic...mentioning
confidence: 99%